A Real-World Comparative Effectiveness Analysis of Thromboprophylactic Use of Enoxaparin Versus Unfractionated Heparin in Abdominal Surgery Patients in a Large U.S. Hospital Database. (February 2022) - Veeranki, S. P.; Xiao, Z.; Levorsen, A.; Sinha, M.; Shah, B.
Introduction: Little is known about outcomes associated with enoxaparin versus unfractionated heparin (UFH) for venous thromboembolism (VTE) prophylaxis in abdominal surgery patients in U.S. clinical practice. The purpose of this study was to compare VTE, all-cause mortality, PE-related in-hospital mortality, and hospital costs during abdominal surgery hospitalization and the 90 days post-discharge between patients who received enoxaparin versus UFH prophylaxis.Materials and Methods: Using the Premier Healthcare Database, abdominal surgery patients who received at least 1 day of VTE prophylaxis with enoxaparin or UFH were identified between January 1, 2010 and September 30, 2016. Clinical outcomes were assessed using multivariable logistic regression models and cost outcomes were assessed using generalized linear models.Results: Of 363, 669 patients identified, 59% received enoxaparin and 41% UFH. In adjusted analyses, there were statistically significant lower odds of VTE (OR 0.80; 95% CI 0.65-0.97), all-cause mortality (OR 0.67; 95% CI 0.60-0.75), and major bleeding (OR 0.88; 95% CI 0.82-0.94) during the hospitalization for enoxaparin versus UFH, but no differences during the 90-days post-discharge or for PE-related mortality. There was a statistically significant lower total hospital cost with enoxaparin versus UFH during index hospitalization (8, 913 vs 9, 017, P < .0001), but not post-discharge (3, 342 vs 3, 368, P = .42). Unadjusted rates of heparin-induced thrombocytopenia (index:0.1% vs 0.3%; post-discharge: 0.02% vs 0.06%) were reported for enoxaparin and UFH, respectively.Conclusion: In contemporary U.S. hospital practice, statistically significant lower odds of VTE, all-cause mortality and major bleeding with enoxaparin versus UFH prophylaxis were found during abdominal surgery hospitalizations.